Method for manufacturing mineral fibers

By adding metal aluminum to mineral raw materials, the restore state of iron oxide is adjusted to solve the problem of excessive contraction of MMVF in the gas fuel blasting furnace, and achieve lower shrinkage and higher fire resistance.

CN119349858APending Publication Date: 2025-01-24ROCKWOOL AS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411469773.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-01-30
Filing Date
2021-01-29
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When manufacturing artificial glass fibers (MMVFs) in cyclone furnaces using gas-fueled gas, the product is prone to excessive shrinkage due to sintering, resulting in the formation of thermal bridges and affecting its fire resistance.

Method used

By adding a small amount of metallic aluminum to the mineral raw materials, the reduction of iron oxide is promoted and the ratio of FeO:Fe2O3 is adjusted, thereby reducing the shrinkage tendency of MMVF.

Benefits of technology

Effectively reduce the shrinkage of MMVF, improve the fire resistance and density of the product, and apply to applications such as fire prevention and heat insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349858A_ABST
    Figure CN119349858A_ABST
Patent Text Reader

Abstract

A method of forming a melt for making artificial vitreous fibers is provided in which a mineral feedstock is melted in a gas cyclone furnace and a mineral aggregate comprises a material comprising metallic aluminum.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This patent application is application number 2021800214117 and application date is January 2021

[0002] On the 29th, a divisional application for a patent application entitled "Method for producing mineral fibers" was filed. Technical Field

[0003] The present invention relates to melting a mineral feedstock to form a mineral melt to produce man-made vitreous fibers (MMVF). Background Art

[0004] Cyclone furnaces for melting mineral raw materials are known in the art. Such furnaces are usually fueled by coal or coke. Cyclone furnaces are, for example, those described in WO03 / 002469 and WO2008 / 019780.

[0005] For a number of reasons, it is preferred to use only gaseous fuel rather than coal or a mixture of multiple types of fuel. Natural gas has a better environmental profile than coal. It can be supplied more sustainably, for example as biogas; its use can be CO2 neutral. Using natural gas may also be beneficial because it is cheaper, at least in part because of lower carbon taxes. Using gas also requires less sulphur dioxide cleaning.

[0006] However, in the case of gas-fired cyclone furnaces, it has been found that the resulting MMVF products can experience excessive shrinkage due to sintering when subjected to high temperatures. Shrinkage can lead to the formation of thermal bridges, which can be critical if the product is used for fire protection. In general, low-density products exhibit greater shrinkage than high-density products.

[0007] It is desirable to provide a method by which a melt suitable for processing into MMVF can be produced which uses a cyclone furnace to provide the melt but which can use a gas fuel without causing excessive shrinkage tendency of the product. Even in the case of a coal-fired cyclone furnace, it is desirable to be able to produce a product with a reduced shrinkage tendency. Summary of the invention

[0008] The above mentioned problems are solved by the process of the present invention, which is a process for producing man-made vitreous fibers (MMVF) comprising at least 3% by weight of Fe 2 O 3 of iron oxide, the method comprising:

[0009] Provide cyclone furnace,

[0010] Providing a mineral raw material, the mineral raw material comprising (a) a material containing metallic aluminum and (b) other mineral components,

[0011] Supply fuel and combustion gases to the cyclone furnace,

[0012] The mineral raw materials are melted in a cyclone furnace to form a mineral melt.

[0013] And MMVF is formed from the melt.

[0014] The present invention is based on the recognition that the shrinkage of the consolidated MMVF product is largely due to the FeO:Fe 2 O 3 In prior art coal fired cyclone furnaces, reducing conditions are created by coal, coke or other carbonaceous particulate fuels. This creates an ideal Fe(II):Fe(III) ratio and therefore the degree of shrinkage of consolidated MMVF products made from melts from coal fired cyclone furnaces is generally within acceptable limits.

[0015] Gas-fired cyclone furnaces do not have the same reducing conditions as coal-fired cyclone furnaces. Fuel types other than coal and coke may encounter the same problems.

[0016] The inventors have realised that this problem can be solved by providing a small amount of metallic aluminium to the mineral raw material (ore). The metallic aluminium reacts with the iron oxide in a highly exothermic manner, thereby reducing Fe(III) and providing Al 2 O 3 , which is an essential ingredient of MMVF chemistry.

[0017] The metallic aluminum source in the present invention may be a material containing 45 wt % to 100 wt % metallic aluminum, for example, a material containing 45 wt % to 99.5 wt % or 45 wt % to 99 wt % metallic aluminum, or aluminum slag.

[0018] Aluminum slag is a granular waste material from the aluminum processing industry, consisting mainly (usually 50 to 90 wt %) of Al 2 O 3 , and about 0.5 wt % to 10 wt % of metallic aluminum. The aluminum slag may account for 5 wt % to 30 wt %, such as about 10 wt %, of the total ore.

[0019] Some sources of aluminum slag include residual ammonia. For these materials, it is preferred to subject the aluminum slag to high temperature treatment, such as a minimum of 800°C, to decompose the ammonia. Lower temperatures will not properly decompose the ammonia, but will produce gaseous ammonia in the exhaust gas stream, which will generally require further treatment to remove the ammonia.

[0020] To remove ammonia, aluminum slag can be injected directly into the top of the cyclone furnace at ambient temperature. The aluminum slag is thus immediately subjected to sufficiently high temperatures to completely decompose any residual ammonia. The aluminum slag can be pre-mixed with other mineral components, but can also be injected directly into the furnace on its own.

[0021] Another optional process step to remove ammonia is to inject the aluminum slag into the hottest part of the cyclone preheater system, whereupon it mixes with the other mineral components that have already been preheated. This optional step is more thermally efficient.

[0022] When the aluminum slag does not contain ammonia or its ammonia content does not constitute a problem at the location of the cyclone furnace, it is preferred to premix the aluminum slag with other mineral components of the ore and feed the total ore as a mixture to the cyclone furnace. This has the benefit of ensuring that the MMVF produced by the present invention has a constant composition.

[0023] The aluminum slag contains 0.5 to 10 wt % of metallic aluminum, 50 to 90 wt % of aluminum oxide Al 2 O 3 and 0 wt % to 49.5 wt % of other materials. Preferably, the aluminum slag contains 2 wt % to 6 wt % of metallic aluminum. Other materials may include SiO 2 , MgO and Fe 2 O 3 Preferably, the aluminum slag comprises oxides of corundum, spinel and mullite.

[0024] The aluminum slag may have a controlled particle size distribution. For example, the aluminum slag may have a particle size distribution such that 90% of the particles by weight are less than 1 mm, preferably 90% of the particles by weight are less than 200 μm. The average particle size of the aluminum slag may be 10 μm to 100 μm, such as 20 μm to 30 μm.

[0025] The content of metallic aluminum and aluminum oxide (and other components) is on a dry basis and can be determined using standard methods. For example, the content of metallic aluminum can be determined by reacting the material with a strong base (such as NaOH). The amount of metallic aluminum can be determined from the amount of hydrogen released.

[0026] Aluminum slag may preferably be a waste product derived from secondary mining of aluminum. In particular, the aluminum casting process provides a special alumina-rich waste material, commonly referred to as "aluminum slag". Aluminum slag often contains a significant proportion of metallic aluminum and is therefore processed to recover metallic aluminum. The aluminum slag is usually crushed, ground and screened. This produces some aluminum for resale and an aluminum-rich portion, which is sent to a furnace for reuse. As a by-product, an alumina-rich powder is also produced. In the method of the present invention, the powder can be used as a source of metallic aluminum. This alumina-rich powder produced by processing aluminum slag (crushed aluminum slag) may contain, for example, 1% to 10%, preferably 1% to 8% of halogen materials (by weight). Halogens include fluorides and chlorides in particular.

[0027] The aluminum-rich fraction, optionally together with other aluminum-containing waste materials, is remelted in a furnace. The furnace may be a rotary furnace or a kiln. The aluminum waste may be subjected to plasma heating. Conventional furnaces may be used. Salt is usually added to the furnace to reduce the surface tension of the aluminum and reduce oxidation. The process produces an aluminum fraction for resale, more aluminum slag and salt slag material. The salt slag may be treated by a wet chemical process (including water washing and high temperature treatment) to produce a salt fraction (which is recycled to the furnace) and a further alumina-rich powder (which may also be used as a metallic aluminum source in the present invention). This product tends to have a lower content of halogen materials (such as fluorides) than the alumina-rich powder produced by aluminum slag treatment (crushed aluminum slag). Its halogen content (by weight) tends to be 0 to 5%, usually at least 0.5% or 1%, preferably not more than 3%.

[0028] As an alternative to aluminum slag, a material containing 45 wt% to 100 wt% of metallic Al may be used as a metallic Al source. Suitable materials are aluminum pellets and one or more blocks of metallic aluminum.

[0029] The block may take any suitable form, such as a rod, strip, pellet or other shape. The block may contain 45% to 100% by weight of aluminum. The aluminum in the rod or other block shape may be inserted directly into the mineral melt in the furnace. This method avoids excessive or premature oxidation of the aluminum before mixing with the mineral bath, thereby improving process efficiency.

[0030] In this case, aluminum pellets (Al pellets) usually require a set of process conditions that are indeed different from aluminum slag. The proportion of metallic aluminum in aluminum pellets is usually much higher than that in aluminum slag. In aluminum slag, metallic Al is replaced by a larger proportion of other components (such as Al 2 O 3 ) is protected from oxidation. Furthermore, the weight percentage of the aluminum slag as a part of the total charge is too high to justify its direct addition to the molten bath: its thermal efficiency will be low. On the other hand, the amount of aluminum pellets required as part of the total charge is much lower, about 0.2% by weight of the total charge, calculated as metallic aluminum, such as 0.1% to 0.5% by weight of the total charge, such as 0.2% to 0.4% by weight of the total charge.

[0031] Therefore, to avoid premature oxidation of the metallic aluminum component, the aluminum pellets are added directly into the molten bath in the cyclone furnace, or directly above the molten bath. This can be described as direct injection. Preferably, the aluminum pellets are added via a burner or lance. Preferably, an oxy-fuel burner with a central tube for transporting the aluminum pellets is used.

[0032] Aluminum pellets may preferably be added above the molten pool surface (eg, at a point within 50 cm of the molten pool surface), preferably 30 cm.

[0033] As a raw material component containing only aluminum pellets, the aluminum pellets can be added alone. Alternatively, it can be pre-mixed with a filler and the mixture of aluminum pellets and filler is added to the furnace as a mixed raw material component. Suitable fillers include various raw materials that can be used as additional raw materials. For example, the aluminum pellets can be mixed with filtered fines (i.e., fine particle raw materials extracted from the exhaust filter of the process) before being injected into the cyclone furnace. In the mixture with the filler, a suitable percentage of aluminum pellets is 1% to 90%, such as 10% to 70%, such as 15% to 50%. Using a mixture of aluminum pellets and other raw materials can improve the dosage control of metallic aluminum in the process.

[0034] Since the density of the melt and metallic aluminum are similar, the aluminum particles are well mixed with the melt.

[0035] Furthermore, aluminum pellets are a purer material than aluminum slag and there are no ammonia removal concerns, for example.

[0036] The particle size (average particle size, where the particle size adopts the maximum dimension of the particle, whether or not the particle is spherical) of the aluminum particles may be no greater than 15 mm, such as less than 10 mm, such as less than 5 mm. In a preferred embodiment, the particle size (average particle size, where the particle size adopts the maximum dimension of the particle, whether or not the particle is spherical) of the aluminum particles may be no greater than 3 mm, such as less than 2 mm, such as less than 1 mm.

[0037] The residence time of the particulate mineral material and the mineral melt in a cyclone furnace is lower than in other types of mineral smelters, so fast reaction kinetics are important in this process.

[0038] In a preferred embodiment, the MMVF has the following element contents, expressed in wt. % of oxides:

[0039] SiO 2 : At least 30, 32, 35 or 37; not more than 51, 48, 45 or 43

[0040] CaO: at least 8 or 10; not more than 30, 25 or 20

[0041] MgO: at least 2 or 5; not more than 25, 20 or 15

[0042] FeO (including Fe 2 O 3 ): At least 4 or 5; not more than 15, 12 or 10

[0043] FeO+MgO: at least 10, 12 or 15; not more than 30, 25 or 20

[0044] Na 2 O+K 2 O: 0 or at least 1; not more than 10

[0045] CaO+Na 2 O+K 2 O: At least 10 or 15; no more than 30 or 25

[0046] TiO 2 : 0 or at least 1; not more than 6, 4 or 2

[0047] TiO 2 +FeO: at least 4 or 6; not more than 18 or 12

[0048] B 2 O 3 : 0 or at least 1; not more than 5 or 3

[0049] P 2 O 5 : 0 or at least 1; not more than 8 or 5

[0050] Others: 0 or at least 1; not more than 8 or 5.

[0051] The fibers preferably have a sintering temperature above 800°C, more preferably above 1000°C.

[0052] The MMVF prepared by the method of the present invention preferably has the following composition, in wt %:

[0053] SiO 2 35 to 50

[0054] Al 2 O 3 12 to 30

[0055] TiO 2 Up to 2

[0056] Fe 2 O 3 3 to 12

[0057] CaO 5 to 30

[0058] MgO up to 15

[0059] Na 2 O 0 to 15

[0060] K 2 O 0 to 15

[0061] P 2 O 5 Up to 3

[0062] MnO up to 3

[0063] B 2 O 3 Up to 3.

[0064] Another preferred composition of MMVF is as follows, in wt %:

[0065] SiO 2 39% to 55%, preferably 39% to 52%,

[0066] Al 2 O 3 16% to 27%, preferably 16% to 26%,

[0067] CaO 6% to 20%, preferably 8% to 18%,

[0068] MgO 1% to 5%, preferably 1% to 4.9%,

[0069] Na 2 O 0% to 15%, preferably 2% to 12%,

[0070] K 2 O 0% to 15%, preferably 2% to 12%,

[0071] R 2 O(Na 2 O+K 2 O) 10% to 14.7%, preferably 10% to 13.5%,

[0072] P 2 O 5 0% to 3%, preferably 0% to 2%,

[0073] Fe 2 O 3 (iron total) 3% to 15%, preferably 3.2% to 8%,

[0074] B 2 O 3 0% to 2%, preferably 0% to 1%,

[0075] TiO 2 0% to 2%, preferably 0.4% to 1%,

[0076] Others 0% to 2.0%.

[0077] SiO 2 The preferred range of CaO is 39% to 44%, especially 40% to 43%. The preferred range of CaO is 9.5% to 20%, especially 10% to 18%.

[0078] Al 2 O 3 The content is preferably between 16% and 27%, preferably greater than 17% and / or preferably less than 25%, SiO 2 and Al 2 O3 The sum of the alkali metal (sodium and potassium) oxides (R 2 The amount of magnesium oxide is preferably relatively high, but is limited to 10% to 14.7%, preferably 10% to 13.5%, wherein the amount of magnesium oxide is at least 1%.

[0079] Preferably, by weight, Al 2 O 3 The content of magnesium oxide is 17% to 25%, in particular 20% to 25%, in particular 21% to 24.5%, especially about 22% to 23% or 24%. Advantageously, the magnesium oxide content is at least 1.5%, in particular 2%, preferably 2% to 5%, particularly preferably >2.5% or 3%.

[0080] By weight, in Al 2 O 3 When the content of Al is at least 22%, the amount of magnesium oxide is preferably at least 1%, advantageously about 1% to 4%, preferably 1% to 2%, and in particular 1.2% to 1.6%. In order to maintain a sufficiently low liquidus temperature, Al 2 O 3 The content of Al is preferably limited to 25%. 2 O 3 When the content is lower, for example, about 17% to 22%, the amount of magnesium oxide is preferably at least 2%, especially about 2% to 5%.

[0081] The total amount of Fe and Mg oxides is important in controlling the shrinkage of MMVF insulation. In addition, the ratio of Fe(II):Fe(III) affects the insulation performance of MMVF under fire conditions, where oxidation of Fe(II) to Fe(III) is a favorable process.

[0082] Advantageously, the ratio of Fe(II):Fe(III) of the fibers is higher than 2, for example higher than 3. The proportion of Fe(3+) in the MMVF before the fiberizing step is generally less than 5%, preferably less than 3%, based on the total Fe content in the melt. This helps to prevent shrinkage.

[0083] The amounts of Fe(2+) and Fe(3+) can be determined using the formula described in “The ferric / ferrous ratio in basalt melts at different oxygen pressures” (Helgason et al., Hyperfine Interact., 45 (1989), pp. 287 to 294). Method determination.

[0084] The total iron in the entire melt or fiber composition is expressed as Fe based on the total oxides in the melt or fiber. 2 O 3 Calculation. This is the standard method of quoting the amount of iron present in such an MMVF, charge or melt. The FeO and Fe 2 O 3 The actual weight percentage will vary depending on the iron oxide ratio and / or redox state of the melt. For example:

[0085]

[0086]

[0087] Table 1

[0088] Thus, one skilled in the art will appreciate that the actual weight percent of iron oxide present will depend on the ratio of Fe(2+) to Fe(3+).

[0089] Any suitable method may be used to form the MMVF from the mineral melt. In particular, an external centrifugal (cascade spinneret) or an internal centrifugal (spinning rotor) may be used.

[0090] In the method of the present invention, any suitable fuel can be used, such as methane, propane, other gaseous fuels, oil, coal and other liquid and solid particulate fuels. Preferably, gaseous fuels are used. In a preferred embodiment, biogas is used to reduce the environmental impact of the process.

[0091] In this method, the combustion gas contains oxygen to complete the combustion of the fuel. The combustion gas can be air in its natural composition, pure oxygen or oxygen-enriched air. BRIEF DESCRIPTION OF THE DRAWINGS

[0092] Figure 1 Exemplary layouts of cyclone furnace and cyclone preheater systems are illustrated. DETAILED DESCRIPTION

[0093] Figure 1 A cyclone furnace 1 is shown, comprising a cylindrical top, a frustoconical bottom and a cylindrical base. Preheated mineral material (with or without an ingredient as a source of metallic aluminium) is introduced into the cyclone furnace via a mixed mineral material conduit 3. Fuel is introduced via conduit 2. The mineral material is introduced together with combustion air via conduit 4 and secondary air, which is provided in a compressed air supply 5 and introduced into the cyclone furnace via a lance (not shown) to ensure a thorough mixing of the fuel with the combustion air, while maintaining a circulating motion of the combustion gases and suspended matter within the cyclone furnace 1. The combustion air is then fed to the cyclone furnace 1 through a duct 4 and a duct 5. The duct 6 is fed to the cyclone furnace 1 through a duct 5 and a duct 6 is fed to the cyclone furnace 1 through a duct 7. The duct 8 is fed to the cyclone furnace 1 through a duct 9. Figure 1A small amount of combustion gas and fuel is diverted from the main feed to the top of the cyclone furnace to the bottom of the cyclone furnace by the route shown in 6 and 7. Secondary fuels such as natural gas are also injected into the base of the cyclone furnace through supply 8, such as Figure 1 As shown in 8.

[0094] The fuel is burned in a cyclone furnace in a combustion gas which is preferably pure oxygen or oxygen-enriched air, thereby melting the ore.

[0095] When aluminum slag is used as a source of metallic aluminum, the aluminum slag may be mixed with other mineral components and then supplied to the silo 19. The ore (including the aluminum slag) from the silo 19 is supplied to the second conduit 14 and initially preheated in the second cyclone preheater 13. The ore is then introduced into the first conduit 11 and subsequently passes through the first cyclone preheater 12. The benefit of this option is that it is easy to maintain a stable relationship between the metallic aluminum content and the other mineral components of the ore.

[0096] Alternatively, when aluminum slag is used as a source of metallic aluminum, the aluminum slag can be provided to the silo 20 at ambient temperature and from the silo 20 to a first downstream conduit to provide the other mineral components of the ore feed, which is provided by the silo 19 as described above in the first option. The aluminum slag is mixed with the other mineral components preheated in the gas stream. This option is useful when the aluminum slag contains some residual ammonia and there is a limit on the amount of ammonia in the flue gas.

[0097] Another option is to add the aluminium slag directly to the cyclone furnace 1 at line 3. This option is less thermally efficient but does ensure complete decomposition of any residual ammonia in the aluminium slag due to the high temperatures in the cyclone furnace 1.

[0098] When aluminum pellets or aluminum blocks are used as the metallic aluminum source, the metallic aluminum is directly added to the cyclone furnace 1 .

[0099] Aluminium metal may be provided as aluminium pellets and added via an oxy-fuel burner with a central injection lance for the aluminium metal at position 8. Other mineral feed is provided from silo 19 and preheated as described above.

[0100] Alternatively, the aluminum metal may be provided in bulk form, in the form of rods, bars or pellets. The aluminum in bulk form is preferably added to the cyclone furnace separately from the granular mineral feedstock, and may be added directly to the molten bath. Smaller aluminum blocks may be injected into the furnace through the burner ports. Larger aluminum blocks may be injected into the furnace from an inlet at the top of the furnace. Bulk aluminum may be blown or otherwise injected directly into the molten bath at the base of the furnace; it may be preferred to minimize oxidation of the aluminum in the circulating gases within the furnace, thereby maximizing the effect of the aluminum metal interacting with the other mineral components.

[0101] In all cases, the ore material is melted in the cyclone furnace 1, and the resulting ore melt is collected in the base area of ​​the cyclone furnace 1 and leaves the furnace through the outlet 9. The exhaust gases generated by the combustion of the fuel are fed through a flue 10 at the top of the circulating combustion chamber to a first duct 11, in which the exhaust gases are used to heat the ore material. The exhaust gases then flow to a first cyclone preheater 12, in which they are separated from the ore material. From the first cyclone preheater 12, the exhaust gases flow through a second duct 14 to a second cyclone preheater 13. After the second cyclone preheater 13, the exhaust gases flow through a duct 15 to a dust cyclone 16 and into a chamber 17, where indirect heat exchange with the combustion gases takes place to preheat the combustion gases. The exhaust gases are then treated so that they can be safely discharged to the atmosphere through, for example, a filter 18 and (if necessary) a desulfurization device. Filtered fines can be collected from the filter 18 and recycled to the furnace 1.

[0102] Some of the mineral material may be carried away with the off-gas from the second cyclone preheater 13 via duct 15. This mineral material is separated from the off-gas in the dust cyclone 16 and recycled back via duct 22 to join the preheated mineral material.

[0103] The exhaust gases leave the circulating combustion chamber through a flue 10. The exhaust gases enter a first duct 11 and are quenched by quench air from a temperature between 1500°C and 1900°C (typically about 1650°C) to a temperature between 900°C and 1200°C (normally about 1100°C). Providing hot exhaust gases at a temperature above 800°C is beneficial, particularly when it is necessary to remove ammonia from the aluminium slag prior to melting.

[0104] As is known, the raw materials for the other mineral components used as the feed can be selected from a variety of sources. These include basalt, diabase, nepheline syenite, cullet, bauxite, quartz sand, limestone, borax, sodium tetraborate, dolomite, soda, olivine sand, potash. Waste materials can also be used.

[0105] MMV fibers can be made from mineral melts in a conventional manner. Typically, they are made by a centrifugal fiberization process.

[0106] For example, the fibers can be formed by a spinning rotor process, in which they are thrown outward through holes in the spinning rotor. The melt is fiberized by the spinning rotor technology (sometimes also called internal centrifugation). Before being directed to the spinning rotor, the melt preferably has a temperature in the range of 1260° C. to 1300° C. at the end of the feeder channel. When the melt is transferred from the feeder channel to the inner part of the spinning rotor, it is preferably cooled down so that the temperature of the melt when flowing through the holes of the spinning rotor is in the range of 1150° C. to 1220° C.

[0107] The viscosity of the melt in the spinning rotor is in the range of 50 Pa.s to 400 Pa.s, preferably in the range of 100 Pa.s to 320 Pa.s, and more preferably in the range of 150 Pa.s to 270 Pa.s. If the viscosity is too low, fibers of a desired thickness cannot be formed. If the viscosity is too high, the melt does not flow through the holes in the spinning rotor at an appropriate discharge rate, which may cause clogging of the holes in the spinning rotor.

[0108] The melt is preferably fiberized by a spinning rotor process at a temperature between 1160° C. and 1210° C. At the spinning temperature, the viscosity of the melt is preferably in the range of 100 Pa.s to 320 Pa.s.

[0109] In another fiber forming process, the melt may be thrown from a rotating disk and fiber formation may be promoted by passing a jet of injected gas through the melt.

[0110] In a preferred method, fiber formation is performed by pouring the melt onto the first rotor in a cascade spinneret. In this case, the melt is preferably poured onto the first of a set of two, three or four rotors, each rotating about a substantially horizontal axis, whereby the melt on the first rotor is primarily thrown onto the second (lower) rotor, although some may be thrown off the first rotor in the form of fibers, and the melt on the second rotor is thrown off in the form of fibers, although some may be thrown toward the third (lower) rotor, and so on.

[0111] MMVF can be collected and consolidated to form a consolidated product comprising MMVF. Typically, such products may include additional ingredients, such as a binder, wherein MMVF is the main ingredient. The fibers produced by the spinning process are preferably collected on a conveyor belt. The binder can be applied to the MMVF in the fiberization process or after fiberization. The binder can be applied by spraying the MMVF. The conventional type of binder used with rock wool fibers can be used. The binder is then cured to produce a final product. The MMVF with a binder is typically cured in a curing oven, typically by a hot air stream. A hot air stream can be introduced into the MMVF with a binder from below or above or from alternating directions in different regions in the length direction of the curing oven. After curing, the cured binder composition bonds the fibers to form a structurally adhered fiber matrix.

[0112] The MMVF may be consolidated after collection, for example by cross-lapping and / or longitudinal compression and / or vertical compression in a known manner. Typically consolidation occurs before the binder cures.

[0113] The MMVF produced by the method of the present invention and the MMVF of the present invention have excellent fire resistance at 1000°C. The MMVF can be made into products for any conventional application of MMVF (e.g., sound insulation or heat insulation or fire protection). Such products include insulation products such as insulation wool, particles, boards, rolls, pipe sections, and other products such as ceiling tiles, wall tiles, facade components, acoustic components and loose fibers. The product can be used in high temperature environments, such as at least 400°C to as high as 1000°C.

[0114] The product may have any density known in the art for the relevant application. For example, the density may be 20 kg / m 3 Up to 1200kg / m 3 In the range of 20kg / m 3 Up to 300kg / m 3 In the range of 20kg / m 3 Up to 150kg / m 3 All product types have advantages in terms of shrinkage, but it has been observed that when the density of the product is relatively low (e.g. not more than 50 kg / m 3 ), a particularly good reduction in shrinkage can be seen.

[0115] Any preferred feature disclosed in this application may be combined with any other preferred feature.

[0116] Example

[0117] Example 1

[0118] A control sample of consolidated MMVF product was prepared from a mineral melt (control material) having the following composition:

[0119] <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[TiO 2 ]]> <![CDATA[Fe 2 THE 3 ]]> FeO CaO MgO <![CDATA[Na 2 The]]> <![CDATA[K 2 The]]> <![CDATA[P 2 THE 5 ]]> MnO 42,6 18,5 0,5 6,9 0,0 18,9 9,2 1,9 0,8 0,2 0,5

[0120] Table 2

[0121] The density of the manufactured control consolidated product was 30 kg / m 3 .according to Figure 1 The mineral melt is prepared in a cyclone furnace.

[0122] A sample of the consolidated MMVF product of the present invention was produced using MMVF spun from a feedstock having the composition of Table 2, to which 0.4 wt. % of aluminum particles (equivalent to 0.2 wt. % of metallic aluminum) were added. In addition to all the components listed in Table 2, the aluminum particles were added. The density of the example product was also 30 kg / m 3 .

[0123] The area shrinkage of the control product and the example product was measured according to an internal test method consisting of 5 steps:

[0124] 1) Cut, measure and weigh the test samples from the product test unit;

[0125] 2) Select representative test samples from the test unit;

[0126] 3) Remove the binder at 590°C;

[0127] 4) sintering the test sample at 1000°C + / - 20°C for 30 minutes; and

[0128] 5) Measure the area of ​​the test sample after sintering.

[0129] Shrinkage is measured as the percentage reduction in surface area of ​​each product. Shrinkage is measured on the principal surface of each product, which is the main surface that is visible in the finished product. For example, the reduction in length and width of a board is measured, but not its thickness.

[0130] Relative area shrinkage between raw material charges with and without aluminum pellets added

[0131]

[0132] Table 3 – Aluminum Pellets Test

[0133] Example 2

[0134] The preparation method of the control sample is the same as that of Example 1.

[0135] The preparation method of the sample of the present invention is the same as that of the control sample, but aluminum slag is added.

[0136]

[0137]

[0138] Table 4 – Aluminium slag test

Claims

1. A method of making a man-made vitreous fiber (MMVF) comprising at least 3% by weight of iron oxide measured as Fe2O3, the method comprising: Provide cyclone furnace, Providing a mineral raw material, the mineral raw material comprising (a) a material containing metallic aluminum and (b) other mineral components, providing fuel and combustion gas to the cyclone furnace, wherein the fuel is gaseous, melting the mineral raw material in the cyclone furnace to form a mineral melt, And an MMVF is formed from the melt.

2. The method according to claim 1, wherein the material comprising metallic aluminum is in granular form.

3. The method according to claim 1 or claim 2, wherein the material containing metallic aluminum is aluminum slag.

4. The method according to claim 3, further comprising: providing a cyclone preheater system connected to the cyclone furnace, The formation of hot exhaust gases in the cyclone furnace, and conveying hot exhaust gas from the cyclone furnace to the cyclone preheater system, The aluminum slag enters the cyclone preheater system before being melted in the cyclone furnace, so that the aluminum slag is preheated before the melting step.

5. The method according to claim 4, wherein the cyclone preheater system comprises a first cyclone preheater and a second cyclone preheater, wherein the exhaust gas is conveyed from the cyclone furnace to the first cyclone preheater and from the first cyclone preheater to the second cyclone preheater, and from the second cyclone preheater to an exhaust port, The aluminum slag is mixed with the other mineral components, and the resulting mineral raw material is introduced into the second cyclone preheater, transported from the second cyclone preheater to the first cyclone preheater, and then transported from the first cyclone preheater to the cyclone furnace.

6. The method of claim 4, wherein the cyclone preheater system comprises a first cyclone preheater and a second cyclone preheater, wherein the exhaust gas is conveyed from the cyclone furnace to the first cyclone preheater and from the first cyclone preheater to the second cyclone preheater, and from the second cyclone preheater to an exhaust port, wherein the other mineral components are introduced into the second cyclone preheater and transported from the second cyclone preheater to the first cyclone preheater, wherein the aluminum slag is introduced into the first cyclone preheater and mixed with other mineral components in the exhaust gas stream to form the mineral feedstock, and The mineral raw material is transported from the first cyclone preheater to the cyclone furnace.

7. The method according to any one of claims 2 to 6, wherein the aluminum slag contains 0.5 to 10 wt% of metallic aluminum and 50 to 90 wt% of aluminum oxide.

8. The method according to any one of claims 1 to 7, wherein 5 to 30 wt. % of the mineral raw material is aluminum slag. 9 . The method according to claim 1 , wherein the material containing metallic aluminum is a material containing 45 wt % to 100 wt % metallic aluminum.

10. The method according to claim 9, wherein the material comprising metallic aluminum is aluminum pellets.

11. The method of claim 10, wherein the aluminum pellets are added by direct injection into the cyclone furnace.

12. The method according to any one of the preceding claims, wherein the mineral feedstock contains 0.1 to 0.5 wt. % metallic aluminum.

13. A method according to any one of the preceding claims, wherein the fibres have a ratio of Fe(II):Fe(III) greater than 2, such as greater than 3.

14. The method of any one of the preceding claims, further comprising consolidating the MMVF to form a consolidated product comprising the fibers.

15. The method according to any one of the preceding claims, wherein the MMVF has the following oxide content, in wt %:

Citation Information

Patent Citations

  • Process and apparatus for making mineral fibres

    WO2003002469A1

  • Process and apparatus for making mineral fibres

    WO2008019780A1

  • Process and apparatus for making a mineral melt

    CN101980972A

  • Melt composition for the production of man-made vitreous fibres

    CN104203851A

  • Method for producing inorganic fiber by utilizing industrial solid waste such as aluminum ash

    CN109809700A